Nanomaterials and Surface Technologies, Materials Applications : Selected, Peer Reviewed Papers from the German-Russian Young Scientists Conference ''Renewable Energy - Biotechnology - Nanotechnology'', May 20-22, 2014, Tomsk, Russia. - Petrashova, Tamara; Bogdan, Anna; Khorechko, Uliana (Advanced materials research ;, 2015)
Collection of selected, peer reviewed papers from the German-Russian Young Scientists Conference "Renewable Energy - Biotechnology - Nanotechnology", May 20-22, 2014, Tomsk, Russia. The 12 papers are grouped as follows: Chapter 1: Nanomaterials and Technologies; Chapter 2: Surface and Coating Materials Technologies and Engineering; Chapter 3: Renewable Energy Materials Application, Thermal Materials Engineering, Biomaterials. This is a selection of peer-reviewed papers from the German-Russian Young Scientists Conference on Renewable Energy, Biotechnology and Nanotechnology in Tomsk, Russia in May 2014